COMPARATIVE ANALYSIS OF ANTIOXIDANT PROFILES OF BARK, LEAVES AND SEEDS OF SYZYGIUM CUMINI (INDIAN BLACKBERRY) - Haroon, Rabbeya; SeemalJelani; Arshad, FakihaKomal (International Journal of Research -GRANTHAALAYAH, 2015)
Syzygiumcumini plant is well known for its medicinal values. This study focuses on the comparative antioxidative capacity of bark, leaves and seeds of Syzygiumcumini plant.Several fractions were made from the crude methanolic extract of bark, leaves and seeds in n-hexane, chloroform, ethyl acetate and butanol and aqueous.Leaves aqueous fraction showed highest phenolic content of 253.6 ± 0.025mg/mL while seed aqueous showed maximum flavonoid content of 0.732 ± 0.0005 mg/mL among all extracts. Bark Ethyl acetate fraction via reducing power assay showed absorbance 3.27 ± 0.19 abs and methanolic and Ethyl acetate fraction of leaves via phosphomolybdate assay showed maximum reducing strength of 15.97 ± 0.008 and 15.97 ± 0.037 mg/mL respectively among all. Seed Chloroform fraction showed maximum TEAC value of 6.28 whereas, Ethyl acetate leaves fraction has shown maximum DPPH inhibition. Where, Hexane fraction of bark showed maximum antioxidant consumption against peroxyl radical at 1.24 at 500 nm among all.The results of the assays showed that, in general, all the extracts of Syzygiumcuminiposses considerable antioxidant and radical scavenging properties, however, polar fractions of all three samples i.e., aqueous and ethyl acetate have exhibited a remarkable antioxidant behavior in all the antioxidant assays.